The integration of Artificial Intelligence and Robotics Technologies in Teaching Social and Cognitive Skills to Children with ASD - Syriopoulou, Christine; Hatzigiannakoglou, Paul; Apostolidou, Elpida (Technium Social Sciences Journal, 2025)
This study investigates the ethical, educational, and methodological implications of using artificial intelligence (AI) and robotics in supporting children with Autism Spectrum Disorder (ASD) within educational settings. It explores both the potential benefits and the limitations of these technologies in fostering cognitive and social skills development. The research is based on a critical literature review of current empirical studies concerning the application of AI and robotic tools in special education for children with ASD. The selection of studies adhered to strict inclusion criteria, focusing on those conducted within formal or informal educational contexts. Emphasis was placed on methodological transparency, evaluation criteria, and the socio-cultural context of implementation. Findings reveal promising opportunities for differentiated instruction, personalized learning, and low-anxiety skill repetition through AI and robotics. However, significant concerns remain regarding data privacy, algorithmic bias, and the reduction of human interaction, which is crucial for emotional and social development. The limited number of high-quality studies and small, culturally homogeneous samples also pose challenges to the generalizability of the results. The study highlights the necessity of ethically responsible, inclusive, and pedagogically sound technological integration in special education. Future research should prioritize large-scale, cross-cultural, and longitudinal studies, integrating interdisciplinary collaboration among educators, psychologists, AI specialists, and developmental experts. The effective use of AI should complement rather than replace human interaction, reinforcing inclusive education practices that center on the needs of children and families.